2010
DOI: 10.1021/ic100272y
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Bis(dichalcogenophosphinate)s and a Remarkable [Li8(OH)6]2+ Polyhedron

Abstract: The synthesis and characterization of three lithium complexes of novel bis(dichalcogenophosphinate) ligands are reported: (PhP(S) 2 CH 2 CH 2 P(S) 2 Ph)Li 2 (THF) 4 (2), (PhP(Se) 2 CH 2 CH 2 P(Se) 2 Ph)Li 2 (THF) 4 .(PhP(Se) 2 CH 2 CH 2 P(Se) 2 Ph)Li 2 (THF) 6 (3) and [PhP(Te) 2 CH 2 CH 2 P(Te) 2 Ph][Li 8 (OH) 6 (THF) 8 ] (4). The synthetic route to these complexes proceeds via the insertion reaction of elemental chalcogens into the phosphorus-lithium bonds of 1,2-dilithio-1,2-di(phenylphosphine)ethylene (1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…151 The structure of the related dianion [PhP(Te) 2 CH 2 CH 2 P(Te) 2 Ph] 2− has been determined in a salt with the octanuclear cluster counterion [Li 8 (OH) 6 (THF) 8 ] 2+ . 152 In their early work, Bildstein and Sladky showed that the reaction of tellurium with diorganylphosphides takes place even when the phosphide is coordinated to a Lewis acid to give the adducts (L)PR 2 Te − (R = Ph, L = BH 3 ; R = t Bu, Cr(CO) 5 ). 150 More recently, Wagner and co-workers obtained the potassium salts of [(H 3 B)PR 2 Te] − [H 3 B•40, R = Ph, t Bu] in almost quantitative yields and structurally characterized the [K(18crown-6)] + adducts; the anionic ligand in the R = Ph derivative binds to K + through the B atom as well as the Te center.…”
Section: Tellurophosphinites and Ditellurophosphinatesmentioning
confidence: 99%
“…151 The structure of the related dianion [PhP(Te) 2 CH 2 CH 2 P(Te) 2 Ph] 2− has been determined in a salt with the octanuclear cluster counterion [Li 8 (OH) 6 (THF) 8 ] 2+ . 152 In their early work, Bildstein and Sladky showed that the reaction of tellurium with diorganylphosphides takes place even when the phosphide is coordinated to a Lewis acid to give the adducts (L)PR 2 Te − (R = Ph, L = BH 3 ; R = t Bu, Cr(CO) 5 ). 150 More recently, Wagner and co-workers obtained the potassium salts of [(H 3 B)PR 2 Te] − [H 3 B•40, R = Ph, t Bu] in almost quantitative yields and structurally characterized the [K(18crown-6)] + adducts; the anionic ligand in the R = Ph derivative binds to K + through the B atom as well as the Te center.…”
Section: Tellurophosphinites and Ditellurophosphinatesmentioning
confidence: 99%
“…Preparation of 1,3-( t BuPLiCH 2 ) 2 C 6 H 4 •TMEDA (8). An aliquot of n BuLi (1.86 mL, 1.73 M in hexanes, 3.22 mmol) was added dropwise via syringe to a solution of 2 (455 mg, 1.61 mmol) in toluene (40 mL) at 0 °C.…”
Section: Synthesis and Characterisationmentioning
confidence: 99%
“…The compound 1,2-(PhPLi) 2 C 6 H 4 has also been used to synthesize dichalcogenophosphinate derivatives by reaction with selenium or tellurium. 8 The coordination chemistry of phosphido ligands is vastly different from that of neutral phosphines, which only have one lone pair and are typically π-accepting. Phosphido centres feature two lone pairs, and hence have a propensity for π-donation, making them suitable for coordination to electron-deficient early transition metals and prone to bridging bonding motifs.…”
Section: Introductionmentioning
confidence: 99%
“…62 The synthesis and characterisation of three lithium complexes of novel bis(dichalcogenophosphinate) ligands have been reported through insertion reactions of elemental chalcogens into the phosphorus-lithium bonds of 1,2-dilithio-1,2-di(phenylphosphine)ethylene. 63 The structural characterisation of two monomeric lithium uranyl-peroxide salts, Li 26 have been obtained from aqueous-alcohol solutions rather than the analogous aqueous solutions from which lithium uranyl-peroxide clusters were isolated. 64…”
Section: Lithiummentioning
confidence: 99%